2019
DOI: 10.1002/ajmg.a.61192
|View full text |Cite
|
Sign up to set email alerts
|

Acromesomelic dysplasia Maroteaux‐type in patients from Vietnam

Abstract: Acromesomelic dysplasias are rare skeletal disorders leading to severe short stature and abnormal skeletal morphology. Acromesomelic dysplasia Maroteaux-type is caused by homozygous or compound heterozygous pathogenic variants in NPR2 that encodes for natriuretic peptide receptor B. Here, we reported the first AMDM case in South East Asia and identified a novel pathogenic variant in NPR2 (c. 152T>C, p. (Leu51Pro)). Further analyses reveal the parents and two other family members were heterozygous for the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…To date, a total of 102 NPR2 variants (82 pathogenic and 20 likely pathogenic) have been reported in ClinVar database (https://www.ncbi.nlm.nih.gov/clinvar). Of them, about 40 homozygous or compound heterozygous NPR2 variants are associated with AMDM [2,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In this study, clinical and molecular findings of 26 patients from 22 unrelated families with a clinical diagnosis of AMDM are evaluated and genotype-phenotype correlations are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a total of 102 NPR2 variants (82 pathogenic and 20 likely pathogenic) have been reported in ClinVar database (https://www.ncbi.nlm.nih.gov/clinvar). Of them, about 40 homozygous or compound heterozygous NPR2 variants are associated with AMDM [2,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In this study, clinical and molecular findings of 26 patients from 22 unrelated families with a clinical diagnosis of AMDM are evaluated and genotype-phenotype correlations are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…К основным клиническим проявлениям АМДМ относятся диспропорциональный нанизм, укорочение конечностей, главным образом за счет уменьшения длины предплечий, голеней и кистей. В большинстве описанных случаев не отмечалось интеллектуального дефицита и патологии других органов и систем [1,2,3,4,5,6,7,8]. При рентгенологическом обследовании в типичных случаях отмечаются укорочение и деформация длинных трубчатых костей с гипоплазией дистального от-дела локтевой кости, подвывихом/вывихом головки лучевой кости, а также клиновидная деформация позвонков, укорочение и расширение пястных костей и фаланг пальцев [9,10,11].…”
Section: сLinical and Radiological Characteristics Of Two Patients With Acromesomelic Dysplasia Maroteaux Type With New Mutation In The Nunclassified
“…Subsequently, several studies showed that homozygous or compound heterozygous mutations of the NPR2 gene caused a severe and disproportionate short stature, whereas heterozygous mutations of this gene seemed to be associated with mild and variable growth impairment without a distinct skeletal phenotype (Wang et al, 2015). Dozens of homozygous NPR2 mutations causing AMDM, as well as heterozygous NPR2 mutations causing idiopathic short stature (ISS), have since been reported (Hwang et al, 2020; Irfanullah et al, 2018; Tran et al, 2019; Wang et al, 2015). However, only two families have been reported as having a heterozygous NPR2 gene c.2455C>T mutation (NM_003995.3( NPR2 ):c.2455C>T p.(Arg819Cys)) causing ISS.…”
Section: Introductionmentioning
confidence: 99%